Różnice w przedwczesnej umieralności w mieście i na wsi w wybranych województwach w 2000 roku - Majczak, Joanna (Differences of Premature Mortality in Urban and Rural Areas of Chosen Provinces of Poland in 2000, 2007)
Many vital processes show in Poland spatial differences, among others premature mortality and the number of lost years of life. Especially significant differences can be observed among urban and rural areas, both in general premature mortality as well as in specific causes of premature mortality. The paper presents the results of estimation of the magnitude of the differences of the number of lost years of life among urban and rural areas in the whole country and in provinces of Poland with the use of WHO methodology; the number of lost years of working life was also estimated. The results of the study support the hypothesis of spatial differences of premature mortality among urban and rural areas in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 175-187